Time computations in anuran auditory systems - Rose, Gary J. (Frontiers in Physiology, 2014)
Temporal computations are important in the acoustic communication of anurans. In many cases, calls between closely related species are nearly identical spectrally but differ markedly in temporal structure. Depending on the species, calls can differ in pulse duration, shape and/or rate (i.e., amplitude modulation), direction and rate of frequency modulation, and overall call duration. Also, behavioral studies have shown that anurans are able to discriminate between calls that differ in temporal structure. In the peripheral auditory system, temporal information is coded primarily in the spatiotemporal patterns of activity of auditory-nerve fibers. However, major transformations in the representation of temporal information occur in the central auditory system. In this review I summarize recent advances in understanding how temporal information is represented in the anuran midbrain, with particular emphasis on mechanisms that underlie selectivity for pulse duration and pulse rate (i.e., intervals between onsets of successive pulses). Two types of neurons have been identified that show selectivity for pulse rate: long-interval cells respond well to slow pulse rates but fail to spike or respond phasically to fast pulse rates; conversely, interval-counting neurons respond to intermediate or fast pulse rates, but only after a threshold number of pulses, presented at optimal intervals, have occurred. Duration-selectivity is manifest as short-pass, band-pass or long-pass tuning. Whole-cell patch recordings, in vivo, suggest that excitation and inhibition are integrated in diverse ways to generate temporal selectivity. In many cases, activity-related enhancement or depression of excitatory or inhibitory processes appear to contribute to selective responses.